Stakeholders’ Engagement Meeting for Developing “Remote sensing- based Information and Insurance for Crops in emerging Economies” (RIICE) in Kenya - Mathieu, Renaud; Satapathy, Sushree (2023)
Through its Work Package 4 “Real-Time Monitoring of Food Systems”, the CGIAR Research Initiative on Digital Innovation and Transformation seeks to improve real time monitoring of food system dynamics to inform multiple stakeholders who make time critical decisions to respond to variation and shocks, improve the flow of information for a better understanding of the food systems, and enhance digital data streams for improving decision making by food system actors. To this end, the International Rice Research Institute (IRRI) in partnership with sarmap organized a Stakeholders’ engagement meeting for presenting and discussing the customization of RIICE (Remote Sensing-based Information and Insurance for Crops in Emerging Economies) for Kenya. The meeting was hosted in PrideInn Azure, in Nairobi on the 5th of September 2023. RIICE is a remote sensing-based digital platform that deliver near real time, geolocalized, accurate, and updated seasonal information on rice production, yield and climate-driven yield losses (www.riice.org). RIICE was developed and operated since 2012 in several Southeast and South Asian countries, including the Philippines, India, Cambodia, and Vietnam. It is currently piloted in Ivory Coast, Mali, Nigeria and Senegal. Through this workshop the Digital Innovation initiative sought to understand national needs and requirements in terms of crop production information and assess the national interest for the implementation of such satellite-based technology to monitor rice crop production in the context of climate change.